2021
DOI: 10.1017/s0022215121000220
|View full text |Cite
|
Sign up to set email alerts
|

Otorhinolaryngological manifestations of coronavirus disease 2019: a prospective review of 600 patients

Abstract: Objectives To evaluate otorhinolaryngological manifestations of coronavirus disease 2019 infection and the time required for their resolution. Methods A prospective analysis was conducted of coronavirus disease 2019 patients presenting from 1 April 2020 to 30 July 2020. The otorhinolaryngological manifestations were evaluated based on patient history. The time required for symptom resolution was evaluated separately for intensive care unit and non-intensive care unit patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(106 reference statements)
1
14
0
Order By: Relevance
“…Unlike the present study, Valentina Parma et al [17] further sub divided loss of taste according to different types of taste sensation (sweet, salt, sour and bitter), with 11% having loss of single taste sensation and 48% having loss of 2 or more taste sensation. Subash Bhatta et al [15] in their study of 600 patients with COVID-19 demonstrated smell disturbance in 63.6% and taste disturbance in 63.5% of the patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unlike the present study, Valentina Parma et al [17] further sub divided loss of taste according to different types of taste sensation (sweet, salt, sour and bitter), with 11% having loss of single taste sensation and 48% having loss of 2 or more taste sensation. Subash Bhatta et al [15] in their study of 600 patients with COVID-19 demonstrated smell disturbance in 63.6% and taste disturbance in 63.5% of the patients.…”
Section: Discussionmentioning
confidence: 94%
“…The COVID-19 targets those cells of the body, which expresses angiotensin-converting enzyme 2 (ACE-2) receptors such as; stratified epithelial cells, type II alveolar cells, absorptive enterocytes from ileum and colon, glial cells and neurons, myocardial cells, bladder urothelial cells, proximal tubule cells of the kidney, oral epithelial cells, and nasal epithelial cells [4][5][6][7][8]. As a result, the COVID-19 infection has very diverse presentation such as, fever, sore throat, cough, breathing difficulty, olfactory and gustatory disturbances, headache, diarrhea, myalgia, rhinorrhea, nasal obstruction, fatigue, post nasal drip, and expectoration [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be inferred that the symptoms were not severe in most of the patients (88.8%). The previous studies in the literature have not described about the aural symptoms in the COVID-19 patients [ 4 , 16 , 41 , 42 ]. The presence of the aural symptoms can be corelated to the inflammation in the nasopharynx of the patients, resulting in deranged functioning of the eustachian tube.…”
Section: Discussionmentioning
confidence: 99%
“…The various studies in the literature have described presentation of the COVID-19 infection without any firm evidence suggesting any one of the presentations as the pathognomic for COVID-19 infection [ 3 , 4 , 9 , 10 , 13 16 ]. The most commonly encountered presenting features are cough, fever, sore throat, head ache, difficulty in breathing, olfactory and gustatory disturbance, diarrhea, myalgia, nasal obstruction, fatigue, rhinorrhea, expectoration and post nasal drip.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in similar cohorts of mostly mild and moderate COVID-19 cases showed prevalence of headache in 66–82% subjects, nasal congestion in 34–68%, nasal discharge in 51–60% and hyposmia/anosmia in 55–70% ( 1 , 3 , 32 ). In our study these numbers were similar for headache (72%), but considerably lower for other nasal symptoms: 30% for congestion, 40% for discharge and 42% for smell impairment.…”
Section: Discussionmentioning
confidence: 74%